La littérature et les arts — Le phénomène de "la correspondance des arts" à travers l'oeuvre journalistique de Zoltán Ambrus (1861–1932) - Bauernhuber, Enikő (Verbum – Analecta Neolatina, 2013)
This paper focusses on the interaction of the various branches of arts through the journalistic works of Zoltán Ambrus. Ambrus was a versatile Hungarian author, interested in the arts, especially painting. He was an outstanding literary critic and translator of the fin-de-siècle, whose literary, journalistic, critical, and translating oeuvre is rich in artistic connections and also in French aspects. The author’s oeuvre provides a good example of how arts, literature and journalism are interconnected in the late 19th century.